Extruded diet macronutrient digestibility: plant-based (vegan) vs. animal-based diets in client-owned healthy adult dogs and the impact of guardian compliance during in-home trials - Liversidge, Brooklynn D.; Dodd, Sarah A. S.; Adolphe, Jennifer L.; Gomez, Diego E.; Blois, Shauna L.; Verbrugghe, Adronie (Frontiers in Animal Science, 2023)
Plant-based (vegan) diets for dogs are commercially available, however, research investigating long-term nutritional adequacy of these diets is scarce. Use of client-owned animals has become increasingly popular for apparent total-tract nutrient digestibility (ATTD) studies, yet low guardian compliance with the study protocol, such as providing daily dietary intake information, is a challenge. However, the impact of low diet reporting compliance on the overall ATTD results is unknown. Sixty-one, client-owned healthy adult dogs completed a randomized, doubleblinded longitudinal study. Dogs were randomly assigned into two groups that were fed either a commercial extruded meat-based diet (MEAT, n=30) or an experimental extruded vegan diet (PLANT, n=31) for 12 weeks. At the end of the study, pet guardians performed a 72-hour total fecal collection for ATTD assessment. Pet guardians were asked to complete a food diary for the duration of the trial, however only a subset of guardians (n=35) provided this food diary at the end of the study. No evidence of an association between pet guardians providing a food diary and apparent digestibility coefficients (ADC) of crude protein (CP) (p=0.14), crude fat (EE) (p=0.72), and dry matter (DM) (p=0.68) was found. Apparent digestibility coefficients for CP (p=0.52), EE (p=0.78), and DM (p=0.43) did not differ between PLANT and MEAT. Body weight and age were found to be associated with CP (p=0.03) and DM (p=0.01) digestibility, but no association with EE (p=0.07) digestibility was present. These results indicate that vegan-and animal-based diets with similar nutrient profiles can have comparable nutrient digestibility. Moreover, presence or absence of a guardian-reported food diary had no effect on the overall results of the ATTD study. Further studies investigating guardian compliance for ATTD trials are needed to develop a standardized protocol and reduce current challenges and limitations related to pet guardian's participation in digestibility trials.